PENGARUH MOTIVASI GELAR, MOTIVASI KUALITAS, MOTIVASI KARIR, DAN MOTIVASI EKONOMI TERHADAP MINAT MAHASISWA AKUNTANSI AKAKOM STEPHEN JAMBI UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI (PPAk) - Feranika, Ayu (JURNAL RISET AKUNTANSI JAMBI, 2019)
This study aims to determine the effect of the degree motivation, quality motivation, career motivation, and economic motivation of the interest in students akakom stephen Jambi in taking part in the accounting profession education. The population in this study is a students akakom stephen jambi accounting major. The sampling technique using sensus method. The data analysis technique used is by using multiple regression. Statistical hypothesis testing using the F and statistical test t. The results showed that : (1)  the degree motivation, quality motivation, career motivation, and economic motivation simultaneously on interest in students akakom stephen Jambi in taking part in the accounting profession education, (2) degree motivation effect on interest in students akakom stephen Jambi in taking part in the accounting profession education, (3) quality motivation effect on interest in students akakom stephen Jambi in taking part in the accounting profession education, (4) career motivation affect on interest in students akakom stephen Jambi in taking part in the accounting profession education, (5) economic motivation not effect on interest in students akakom stephen Jambi in taking part in the accounting profession education.